2001
DOI: 10.1017/s1357729800058148
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of high Alpine grazing conditions for early-lactation cows: effects of energy and protein supplementation

Abstract: In each of 2 years (years A and B), the effects of three nutritional regimes were examined using 12 cows kept at pasture for 77 days at 2000 m above sea level. Two supplement formulations (1 and 2) were designed, both equally high in readily fermentable energy (14·6 MJ metabolizable energy (ME) per kg dry matter (DM)) but differing in crude protein content (53 and 193 g/kg DM). The treatments imposed were either pasture grass alone (control groups; both seasons) or grass and supplements provided at three level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 28 publications
8
37
1
Order By: Relevance
“…The results of this CRC test, performed within experiment II and following the principles outlined by Berry et al [2], confirmed its applicability, particularly when based on early-morning faecal samples [in line with 2,19] and on the C 31 :C 32 ratio. Berry et al [2] noted a slightly higher accuracy with the C 33 :C 32 ratio, but subsequently variability between cows was found to be higher than with the C 31 :C 32 ratio [3], as was also true for the present investigation. Furthermore, as in other studies [24,29], the C 33 alkane content of lowland grass was lower than 50 mg·kg -1 considered as threshold value for the use of n-alkanes as marker.…”
Section: The Accuracy Of the Crc Alkane Technique In Cows Fed Exclusisupporting
confidence: 82%
See 4 more Smart Citations
“…The results of this CRC test, performed within experiment II and following the principles outlined by Berry et al [2], confirmed its applicability, particularly when based on early-morning faecal samples [in line with 2,19] and on the C 31 :C 32 ratio. Berry et al [2] noted a slightly higher accuracy with the C 33 :C 32 ratio, but subsequently variability between cows was found to be higher than with the C 31 :C 32 ratio [3], as was also true for the present investigation. Furthermore, as in other studies [24,29], the C 33 alkane content of lowland grass was lower than 50 mg·kg -1 considered as threshold value for the use of n-alkanes as marker.…”
Section: The Accuracy Of the Crc Alkane Technique In Cows Fed Exclusisupporting
confidence: 82%
“…This study supplements a previous one comparing extremes on the same alpine pasture, namely early-lactating cows and a slow-growing beef breed [40], which were either underfed (dairy) or poorly utilising the feed resources (beef). As expected from the lower level of performance, the average herbage DMI of 16 kg·d -1 (dairy cows) was slightly lower than that found previously in early-lactating dairy cows on the same high-altitude pasture [3,8]. As beef cows had a clearly lower estimated milk yield, their lower intake compared to the dairy cows is reasonable.…”
Section: Feed Intake and Nutrient And Energy Supply From Grass-only Dsupporting
confidence: 53%
See 3 more Smart Citations